2016
DOI: 10.1021/acs.joc.6b01369
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Psychrophilin E

Abstract: The first total synthesis of psychrophilin E, a potent antiproliferative cyclic tripeptide isolated from Aspergillus versicolor ZLN-60, is reported herein. Key features of the synthesis include the installation of an amide bond between the indole-nitrogen of tryptophan and an anthranilic acid residue, and a high yielding macrolactamization of the linear tripeptide to the desired macrocycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…One of these natural structures is (+)-psychrophilin E ( 5 ), a cyclic tripeptide formed by tryptophan, proline, and anthranilic acid residues, the total synthesis of which was published in 2016 by Brimble and co-workers ( Figure 2 ). 5 To the best of our knowledge, this structure represents the only natural product containing a macrolactam ring attached through the indole nitrogen of the tryptophan moiety. We envisioned that the biosynthetic pathway toward this naturally occurring compound would be similar to the biosynthetic pathway toward the new structure proposed for novofumigatamide ( d -Trp-regio- 4 ), with an additional last step for our synthetic target involving the simultaneous formation of the hexahydropyrrolo[2,3- b ]indole core and the prenylation at position C3.…”
Section: Results and Discussionmentioning
confidence: 99%
“…One of these natural structures is (+)-psychrophilin E ( 5 ), a cyclic tripeptide formed by tryptophan, proline, and anthranilic acid residues, the total synthesis of which was published in 2016 by Brimble and co-workers ( Figure 2 ). 5 To the best of our knowledge, this structure represents the only natural product containing a macrolactam ring attached through the indole nitrogen of the tryptophan moiety. We envisioned that the biosynthetic pathway toward this naturally occurring compound would be similar to the biosynthetic pathway toward the new structure proposed for novofumigatamide ( d -Trp-regio- 4 ), with an additional last step for our synthetic target involving the simultaneous formation of the hexahydropyrrolo[2,3- b ]indole core and the prenylation at position C3.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The first total synthesis of psychrophilin E ( 20 ) was completed in 2016 by Brimble et al (Scheme 2). 29 Two routes were published, with the more concise route consisting of six steps with an overall yield of 28%. Dipeptide 25 was synthesized from a protected tryptophan, isatoic anhydride, and a Boc-protected proline residue was then coupled using standard peptide coupling conditions.…”
Section: Natural Products Linked By Tryptophan Substitutionmentioning
confidence: 99%
“…46 In addition, this compound showed stronger cytotoxic activity than cisplatin, a known chemotherapeutic agent (IC 50 = 33.4 μg/mL). 46 Two methods for the synthesis of psychrophilin E (25) were proposed in 2016 by Brimble et al 47 Coupling of indole-3carboxaldehyde 26 to 2-nitrobenzoic acid 27 promoted by DCC gave 28 in 93% yield (Scheme 3). To achieve a high yield in this reaction, the presence of aldehyde in 26 and an onitro group in 27 was necessary, whereas the use of the reduced and protected derivatives of these compounds led to unsatisfactory yields.…”
Section: Cross-linking To Position 1 Of the Indole Of Tryptophanmentioning
confidence: 99%
“…This hypothesis was supported by quantum-chemical calculations, which showed that the 2S-epimer of 25 is 30 kcal/ mol more stable than the 2R-epimer. 47 However, the unreacted 2R-33 was not isolated from the macrocyclization reaction mixture.…”
Section: Cross-linking To Position 1 Of the Indole Of Tryptophanmentioning
confidence: 99%
See 1 more Smart Citation